Atypical presentation of bladder pheochromocytoma - Chen-Yueh Wen; Chung-Tai Yu; Cheng-Hsing Hsieh (Tzu-Chi Medical Journal, 2017)
Bladder pheochromocytoma is a rare tumor. The typical manifestations are hematuria, hypertension, headache, sweating, and tachycardia provoked by micturition or overdistention of the bladder. We herein report a case of bladder pheochromocytoma in a 52-year-old woman who presented without micturition attacks. Her clinical course had a latent period of 10 years. A urinary bladder tumor was found incidentally on magnetic resonance imaging.Cystoscopy revealed a large submucosal tumor covered by congested urothelium with a broad base over the left lateral wall of the bladder. Transurethral resection was performed, and the final diagnosis was confirmed by pathological analysis. The patient remained recurrence free after 7-year follow-up.